Non-perturbative quantization à la Heisenberg: zero flux tube between quark and quark - Dzhunushaliyev, V.D. (Хабаршы. Физика сериясы, 2018)
Non-Abelian version of field distribution between two positive (negative) charges is considered. Using a two-equation approximation in the non-perturbative quantization à la Heisenberg, a flux tube stretched between two quarks (antiquarks) located at  is obtained. The dual Meissner effect is demonstrated by confining of color fields into the tube by a condensate of coset non-Abeian fields. A special case is considered when the longitudinal electric field produced by a quark located at  is equal and oppositely directed to the field generated by a quark located at  that leads to zero total electric field. We show that applying the two-equation approximation in the non-perturbative quantization à la Heisenberg for QCD one can obtain the flux tube stretched between quark and quark (antiquark and antiquark) located at  with zero longitudinal color electric field. It is shown that all color electric and magnetic fields are expelled by the scalar field that describes a condensate of coset non-Abelian fields. This effect is the analog of the Meissner effect in superconductivity for non-Abelian color fields.